Vertical PFAS profiles in Arctic shelf - Rainer Lohmann; Leo Yeung (Arctic Data Center, 2016)
This data set reports concentrations of several poly- and perfluorinated alkyl substances (PFASs) in vertical water column profiles from the Arctic shelf. Samples were collected from seven locations on the Beaufort Chukchi Shelf from surface to bottom (up to 385 m) by the United States Coast Guard icebreaker in October 2012. Concentrations of PFASs in water samples collected along the Arctic shelf at different depths from nearshore to offshore were always dominated by PFOA, followed by PFOS and PFNA. Other PFASs were not routinely detected. Different PFAS composition profiles were observed between the samples collected along the Arctic shelf and the Arctic Ocean.